Hemispheric Activation during Planning and Execution Phases in Reaching post Stroke: A consort study - Fang, Yin (Medicine (Baltimore), 2015)
Enhanced activation in the non-lesion hemisphere in stroke patients was widely observed during movement of the affected upper limb, but its functional role related to motor planning and execution is still unknown. This study was to characterize the activation in the non-lesion hemisphere during movement planning and execution by localizing sources of high-density electroencephalography (EEG) signal and estimating the source strength (current density [A/m(2)]). Ten individuals with chronic stroke and shoulder/elbow coordination deficits and 5 healthy controls participated in the study. EEG (64 channels) was recorded from scalp electrodes while the subjects performed a reach task involving shoulder flexion and elbow extension of the affected (patients) or dominant (controls) upper extremity. Sources of the EEG were obtained and analyzed at 17 time points across movement preparation and execution phases. A 3-layer boundary element model was overlaid and used to identify the brain activation sources. A distributed current density model, low-resolution electromagnetic tomography (LORETA) L1 norm method, was applied to the data pre-processed by independent component analysis. Subjects with stroke had stronger source strength in the sensorimotor cortices during the movement compared with the controls. Their contralesional/lesional activation ratio (CTLR) for the primary motor cortices was significantly higher than that of the controls during the movement-planning phase, but not during the execution phase. The CTLR was higher in planning than in the execution phase in the stroke group. Excessive contralesional motor cortical activation appears to be more related to movement preparation rather than execution in chronic stroke.